Multicenter prospective evaluation of the express view reading mode for small-bowel capsule endoscopy studies - Saurin, Jean-Christophe; Jacob, Philippe; Heyries, Laurent; Pesanti, Christian; Cholet, Franck; Fassler, Isaac; Boulant, James; Bramli, Slim; De Leusse, Antoin; Rahmi, Gabriel; and the French Society of Digestive Endoscopy (SFED) (Endoscopy International Open, 2018)
Background Reducing the reading time of capsule endoscopy films is of high priority for gastroenterologists. We report a prospective multicenter evaluation of an “express view” reading mode (Intromedic capsule system).Methods Eighty-three patients with obscure gastrointestinal bleeding were prospectively included in 10 centers. All patients underwent small-bowel capsule endoscopy (Intromedic, Seoul, Republic of Korea). Films were read in standard mode, then a second reading was performed in express view mode at a second center. For each lesion, the precise location, nature, and relevance were collected. A consensus reading and review were done by three experts, and considered to be the gold standard.Results The mean reading time of capsule films was 39.7 minutes (11 – 180 minutes) and 19.7 minutes (4 – 40 minutes) by standard and express view mode, respectively (P < 1 × 10 – 4). The consensus review identified a significant lesion in 44/83 patients (53.0 %). Standard reading and express view reading had a 93.3 % and 82.2 % sensitivity, respectively (NS). Consensus review identified 70 significant images from which standard reading and express view reading detected 58 (82.9 %) and 55 (78.6 %), respectively. The informatics algorithm detected 66/70 images (94.3 %) thus missing four small-bowel angiodysplasia.Conclusion The express view algorithm allows an important shortening of Intromedic capsule film reading time with a high sensitivity.